Prevalence of severe childhood obesity in Wales UK. (28th November 2019) - Beynon, Claire; Bailey, Linda
Abstract: Background: In Wales, approximately one in eight children is obese (aged 4–5 years). The aim of this prevalence study was to examine the trends in severe childhood obesity and investigate any relationship with socioeconomic deprivation. Methods: Data for all children included as part of the Wales Childhood Measurement Programme (2013/14–2017/18) were utilized. Data on the number who had a body mass index above the 99.6th centile indicating severe obesity were calculated over time by sex and in relation to deprivation. Results: Of the 162 208 children measured between 2013/14 and 2017/18 (mean age 5.06 years, standard deviation 0.35 years), the overall prevalence of severe obesity was 3.1% (95% confidence interval [CI] 3.0–3.2%). This varies from 1.9% (95% CI 1.7–2.1%) in the least deprived areas to 3.9% (95% CI 3.7–4.0%) in the most deprived areas. Boys have higher prevalence of severe obesity than girls: 3.6% (95% CI 3.4–3.9%) of boys ( n  = 598) and 3.0% (95% CI 2.7–3.2%) of girls ( n  = 467) were categorized as severely obese in reception year in Wales in 2017/18. Prevalence has increased over time but this is not statistically significant. Conclusion: This study found significantly higher levels of severe obesity in areas of socioeconomic deprivation. Levels of severe obesity were significantly higher in boys than in girls.